Total fat content and bioactive compounds of different genotypes of garlic (Allium sativum L.), grown in Dominican Republic (Agroindustrial Science, 2025)
Garlic is a widely consumed plant species around the world. In the Dominican Republic there is high genetic diversity in the white and purple garlic varieties cultivated in Constanza, La Vega, with more than twenty genotypes having been cultivated; however, some have disappeared, or their production has been discontinued due to poor adaptability, productivity, or convenience, mainly due to the lack of chemical characterization. In this research, the total fat content and bioactive compounds of the prevailing and cultivated genotypes were analyzed: Taiwan 1, Taiwan 2, Taiwan 3, Taiwan 3A, Taiwan 05, Cuban Morado, Cuban Morado #3, Morado Rosello, Morado Rosello #1, Morado Niño, IDIAF 1, IDIAF SEA 14 and Ramón Collado. A completely randomized design was used, and an ANOVA and Tukey's test were applied at 95% confidence. The results were: total fat (0.08 to 0.38 % dry basis), allicin (167.92 to 2,335.55 mg/kg), antioxidant activity (23.83 to 98.83 μmolTE/100g), total phenolic content (89.70 to 136.85 mgGAE/100g), tannins (293.33 to 535.76 mg TAE/kg) and flavonoids (23.78 to 61.62 μgEqRutin/g). Total fat and bioactive compounds fluctuated between genotypes, highlighting the difference in chemical composition according to their genetic variation.
Keywords: Allium sativum L.; Genotypes; Total Fat; Antioxidant Capacity; Bioactive Compounds